HUBUNGAN PERTIMBANGAN MANFAAT DAN RISIKO, ALAT PEMBAYARAN, DAN TEMPAT BERBELANJA DENGAN PERILAKU KONSUMEN MENJAGA PROTOKOL KESEHATAN - Amelia Kristofani; Agnes Kania; Anastasia Felice; Cindy Cynthia; Jessica Christy; Novita .; Immanuel Yosua; Rayini Dahesihsari (Jurnal Manajemen, 2021)
During the pandemic, consumers are advised to pay attention to health protocols regarding product consumption This study aims to determine the relationship between preferences of evaluating benefit or risk, selection of payment instruments, and places to shop with considerations of health protocols in consumption behavior. To test the hypothesis that payment instruments and places to shop affect the consideration of health protocols in consumer behavior, an online survey was distributed to 1058 participants with age 18-25 years who are currently living in Jakarta, Bogor, Depok, Tangerang, and Bekasi. Responses were analyzed using the Spearman Rank correlatio method. The results showed that the use of cash has a significant relationship with cognitive, affective and behavior dimensions of the health protocol consideration on consumption behavior. However, with the cognitive dimension of health protocol consideration on consumption behavior, the use of cash is negatively correlated. Meanwhile, the choice to shop online has a significant positive correlation with all dimensions of health protocol considerations on consumption behavior. The results indicate that promoting cashless and online consumption are inline with supporting health protocols consideration on consumption behavior.